The effect of soil type and moisture content on head impacts on natural grass athletic fields - Dickson, K.; Strunk, W.; Sorochan, J. (Proceedings, 2018)
Studies are warranted to evaluate head injury criterion (HIC) on athletic fields to determine baseline numbers and compare those findings to current critical thresholds for impact attenuation. A two year (2016 and 2017) study was conducted on University of Tennessee athletic fields (Knoxville, TN, USA) to determine the effect of soil type (cohesive soil, United States Golf Association sand specifications) and grass species (Poa pratensis and Cynodon dactylon × C. transvaalensis) on HIC. Additionally soil moisture conditions monitored were: dry (0.06-0.16 m3/m3), acceptable (0.17-0.29 m3/m3), and wet (0.30-0.40 m3/m3). A linear relationship (r = 0.91) was identified between drop height (0.5-2.9 M) and HIC value (35-1423 HIC) on granular root zones of both grass types. However, HIC on cohesive soil is a function of soil water content in addition to drop height. These results demonstrate to aid in head injury prevention on cohesive soil athletic fields the HIC can be lowered by managing soil water content.